KEEPING THE ENVIRONMENT CLEAN - Students: Rustamova Roziya Nabiyeva Maftuna Teacher: Miss Tohira G’aniyeva (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Annotation: This article analyses contemporary environmental challenges before giving a holistic approach to keeping the environment clean. It evaluates existing perspectives, highlights their limitations, and proposes balanced, future-oriented strategies to ensure sustainable living.